Women's Spirituality Across the Life Span: Implications for Counseling. Issue 1 (4th April 2013) - Briggs, Michele Kielty; Dixon, Andrea L.
<x xml:space="preserve">Abstract</x> Women's spirituality has unique characteristics that are often ignored within the spirituality literature. The authors review the literature on women's spirituality to reveal the major themes women have identified as relevant to their spiritual journeys across the life span. Implications for counseling and ideas for practice are included after major themes are examined.